Innovators, firms, and markets the organizational logic of intellectual property - Barnett, Jonathan M. (Oxford University Press, 2020)
This book presents a theoretical, historical and empirical account of the relationship between intellectual property rights, organizational type and market structure. Patents expand transactional choice by enabling smaller R&D-intensive firms to compete against larger firms that wield difficult-to-replicate financing, production and distribution capacities. In particular, patents enable upstream firms that specialize in innovation to exchange informational assets with downstream firms that specialize in commercialization, lowering capital and technical requirements that might otherwise impede entry. These theoretical expectations track a novel organizational history of the U.S. patent system during 1890-2006. Periods of strong patent protection tend to support innovation ecosystems in which smaller innovators can monetize R&D through financing, licensing and other relationships with funding and commercialization partners. Periods of weak patent protection tend to support innovation ecosystems in which innovation and commercialization mostly take place within the end-to-end structures of large integrated firms. The proposed link between IP rights and organizational type tracks evidence on historical and contemporary patterns in IP lobbying and advocacy activities. In general, larger and more integrated firms (outside pharmaceuticals) tend to advocate for weaker patents, while smaller and less integrated firms (and venture capitalists who back those firms) tend to advocate for stronger patents. Contrary to conventional assumptions, the economics, history and politics of the U.S. patent system suggest that weak IP rights often shelter large incumbents from the entry threat posed by smaller R&D-specialist entities"--